Anti-SARS-CoV-2 IgG seroprevalence among non-vaccinated healthcare workers: a study from rural North India - Mane, Pratibha; Sangwan, Jyoti; Lohan, Kirti (International Journal Of Community Medicine And Public Health, 2021)
Background: Coronavirus disease 2019 (COVID-19) is an infectious disease reported in China initially which spread around the world in no time affecting millions of people. It is caused by a new coronavirus (SARS-CoV-2 or 2019 n-CoV). The healthcare workers (HCW) are at increased risk of acquiring the disease as well as antibody response. Methods: 457 health care workers (HCW) were recruited to give blood samples for anti-SARS CoV-2 IgG testing between September to October 2020. Results: Of the 457 participants, IgG antibodies against SARS-CoV-2 were detected in 116 health care workers (25.4%). The anti-SARS-CoV-2 antibodies were detected maximally in HCWs involved in laboratory work. Around 4 % of health care workers were RT-PCR positive form whom IgG were detected in 15 individuals (71.4%) only. Conclusions: The study concludes a higher prevalence among health care workers involved with patient’s samples and laboratory.